Perceptions of a Statewide Mentor Program for New Itinerant Vision Professionals. (September 2013) - Pogrund, Rona L.; Cowan, Chrissy
Introduction: Mentoring is valuable for the retention of new teachers. This article describes a model statewide mentor program for new itinerant vision professionals who work with students from birth to age 22. The results of a recent survey of satisfaction are reported, along with implications for the field. Methods: The protégés who participated in the statewide mentor program completed an electronic satisfaction survey. Of the 76 participants who had been assigned a mentor during the 2011–12 academic year, 56 responded (74%). Both quantitative and qualitative questions were included in the survey. The quantitative questions were analyzed using percentages, and the qualitative data was analyzed and put into themes using the data analysis process of triangulation. Results: Seventy-one percent of the participants reported having had more than 10 interactions with their mentors over the previous year. The topics most frequently addressed with their mentors were performing evaluations (89%), locating resources (84%), and writing goals and objectives (79%). The most helpful mentoring techniques that were used included guided problem-solving techniques (70%), effective listening (68%), and the provision of teaching materials (57%). The majority of the protégés (82%) thought that their mentors had definitely contributed to the quality of their teaching. The top stressors for new vision professionals were related to organization and time management, evaluations, and collaboration with others. Discussion: The results of the survey demonstrate that the mentor program had a positive outcome for the participants as new educators. It also provided information on the stressors faced by these new vision professionals. Implications for practitioners: This article can serve as a model for other states that are interested in developing a mentor program for new itinerant vision professionals, and can serve as a guide for personnel preparation programs to address further the areas that the protégés identified as those in which they felt the least competent.